(untitled) (Research, Society and Development, 2022)
Biodiversity is not exclusive to the fields of biology and ecology. It is used in several areas, by various social actors, such as politicians, scientists, researchers, activists, economists and teachers. In the educational environment, working with biodiversity is part of Environmental Education. With the publication of the National Curricular Common Base (BNCC) the transversal themes were expanded as Transversal Contemporary Themes, making biodiversity used by various components, including Physical Education. That said, the objective of this review was to know how biodiversity is being addressed within the area of Physical Education, from publications that are indexed in the Google Scholar search database. Therefore, a bibliographic review study on Physical Education and Biodiversity was carried out, using the keywords (or descriptors) “Physical Education and Biodiversity”, “Physical Education and the Environment”, and “Physical Education and Environmental Education”. The work between Physical Education and Biodiversity still seems difficult for the teachers of this component, either because of their basic training or their restricted view of nature. However, it is an opportunity to address the issue of the environment in the classroom. Contact with nature through adventure sports is a great pedagogical tool for teaching Environmental Education. It is expected that more studies about the relationship between Physical Education and Biodiversity will be developed.